Treasury expert and an estimation of an obliged person’s assets which is delivered in the enforce-ment of tax claims - Ireneusz Nowak; Joanna Wyporska-Frankiewicz (Prawo Budżetowe Państwa i Samorządu, 2019)
This article is dedicated to selected issues relating to an institution of a tax expert. This institution is regulated by the Act on enforcement proceedings in the administration. Authors emphasise that a tax expert may prepare opinions in which he/she estimates obligated person’s assets only at the request of the enforcement authority. Such a request may be made during the enforcement procedure. Moreover, Authors postulate to establish an autonomous enforcement procedure in the field of tax liabilities.